Inside Back Cover: Isolated Single Iron Atoms Anchored on N‐Doped Porous Carbon as an Efficient Electrocatalyst for the Oxygen Reduction Reaction (Angew. Chem. Int. Ed. 24/2017). Issue 24 (9th May 2017) - Chen, Yuanjun; Ji, Shufang; Wang, Yanggang; Dong, Juncai; Chen, Wenxing; Li, Zhi; Shen, Rongan; Zheng, Lirong; Zhuang, Zhongbin; Wang, Dingsheng; Li, Yadong
Abstract : Isolated single‐atom iron catalysts with excellent oxygen reduction reaction (ORR) reactivity and outstanding stability are prepared by a cage‐encapsulated‐precursor pyrolysis strategy. In their Communication onpage 6937 ff., D. Wang, Y. Li, and co‐workers show experimentally and theoretically that it is essential for the high ORR performance to maintain the iron centers as isolated atoms as well as to incorporate nitrogen.